Recovery of Staphylococci from Teatcups in Milking Parlours in Goat Herds in Greece: Prevalence, Identification, Biofilm Formation, Patterns of Antibiotic Susceptibility, Predictors for Isolation - Charalambia K. Michael; Daphne T. Lianou; Katerina Tsilipounidaki; Dimitris A. Gougoulis; Themistoklis Giannoulis; Natalia G. C. Vasileiou; Vasia S. Mavrogianni; Efthymia Petinaki; George C. Fthenakis (MDPI AG, 2023)
The objectives of this work are (a) to describe staphylococci on the teatcups of milking parlours in goat farms and identify predictors for the presence of staphylococcal isolates on the teatcups, (b) to evaluate relationships with total bacterial counts and somatic cell counts in bulk-tank milk, and (c) to establish patterns of susceptibility to antibiotics for the staphylococcal isolates and identify predictors for the recovery of resistant isolates. In a cross-sectional study of 66 goat farms across Greece, swab samples were collected from 303 teatcups (upper and lower part) for staphylococcal recovery, identification, and assessment of biofilm formation. Details regarding health management on the farms (including conditions in the milking parlour) and the socio-demographic characteristics of farmers were collected by means of a structured questionnaire. A total of 87 contaminated teatcups (28.7%) were found on 35 goat farms (53.0%). Staphylococci were more frequently recovered from the upper than the lower part of teatcups: 73 versus 43 teatcups, respectively. After identification, 67 staphylococcal isolates (i.e., excluding similar isolates) were recovered from the teatcups; Staphylococcus aureus, Staphylococcus capitis, and Staphylococcus equorum predominated. Of these isolates, 82.1% were biofilm-forming. In multivariable analysis, the annual incidence of clinical mastitis in the herd emerged as the only significant factor associated with the isolation of staphylococci from the teatcups. Of the 67 isolates, 23 (34.3%) were resistant to at least one antibiotic, and 14 (22.4%) were multi-resistant. Resistance was found most commonly against penicillin and ampicillin (22.4% of isolates), fosfomycin (17.9%), clindamycin (14.9%), erythromycin, and tetracycline (13.4%). In multivariable analysis, the annual incidence of clinical mastitis in the herd and the use of detergent for parlour cleaning emerged as significant factors associated with the isolation of staphylococci resistant to antibiotics.